Synthesis of Nb5+ doped TiO2 as visible light photocatalyst via peroxo titanic acid sol approach for self cleaning applications. - Toh, Wei Jian. (2010)
TiO2 has been extensively studied for its photocatalytic activity and photoinduced hydrophilicity, making it an ideal candidate as a self-cleaning surface. This work investigates the effects of doping various concentrations of Nb5+ cations into TiO2 to obtain a uniform TiO2 thin film. Using a novel and “green” precursor known as peroxo titanic acid (PTA) sol, the Nb5+ doped TiO2 samples obtained were organic free, thus increasing its feasibility in many applications. XRD spectra of the samples showed that doping of Nb5+ resulted in no phase transformation of TiO2 from anatase to rutile at annealing temperature of 550oC. The roughness and microstructure of the coatings were examined by Atomic Force Microscopy (AFM) and Field Emission-Scanning Electron Microscopy (FE-SEM), while UV-Vis spectra indicated that all doped samples had visible light absorption ability. FTIR spectra confirmed the existence of peroxo groups in all the samples. Photodegradation tests revealed Nb5+ doping increases photocatalytic activity, reaching an optimal at dopant concentration of 1.0 wt%. Excessive doping of Nb5+ resulted in decreased visible light absorption and photocatalytic activity which may be attributed to the Burstein-Moss effect and increased recombination of charge carriers. Wettability study of the samples showed that all the samples were superhydrophilic one day after they were prepared and wettability was decreased slightly when the samples were tested after being kept in the dark for thirty days. The current Nb5+ doped TiO2 may be feasible as a self-cleaning surface.